Novel "Memang Jodoh" Karya Marah Rusli: Kajian Intertekstual - Nia Kurnia; Silvia Rosa; Muchlis Awwali (Jurnal Elektronik WACANA ETNIK, 2018)
This paper presents the ideological theme of the text Memang Jodoh. The method used is the method of suprasegmental and intertextual. This method tries to find the intertextual functions that exist in the text. This function is a code that is related to social contexts and history.The results show that social and historical texts found in the text Memang Jodoh has similarities or parallels with social and historical contexts which are mamak, kemenakan, inheritance, marriage, uang jemputan, sumando, rumah gadang and rangkiang, malakok, school during colonial era, colonialism, and military aggressions. The social and historical texts are dominated by Minangkabau culture. This dominance illustrates the exclusivity of culture.